2001
DOI: 10.1152/ajplung.2001.280.3.l442
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite stimulates plasma membrane NADPH oxidase in vascular endothelial cells

Abstract: Low-level arsenite treatment of porcine aortic endothelial cells (PAEC) stimulated superoxide accumulation that was attenuated by inhibitors of NAD(P)H oxidase. To demonstrate whether arsenite stimulated NADPH oxidase, intact PAEC were treated with arsenite for up to 2 h and membrane fractions were prepared to measure NADPH oxidase activity. Arsenite (5 microM) stimulated a twofold increase in activity by 1 h, which was inhibited by the oxidase inhibitor diphenyleneiodonium chloride. Direct treatment of isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 38 publications
(72 reference statements)
4
102
0
1
Order By: Relevance
“…Besides phagocytic NADPH oxidase, iAs can also stimulate nonphagocytic NADPH oxidase in endothelial cells (16,34), vascular smooth muscle cells (35), and in the human promyelocytic NB4 cell line (15); however, molecular mechanisms mediating its activation remain poorly understood. Chou et al (15) have shown that prolonged treatment of NB4 cells (9 days) with 0.75 M As 2 O 3 markedly up-regulate mRNA levels and membrane expression of p47 phox .…”
Section: Discussionmentioning
confidence: 99%
“…Besides phagocytic NADPH oxidase, iAs can also stimulate nonphagocytic NADPH oxidase in endothelial cells (16,34), vascular smooth muscle cells (35), and in the human promyelocytic NB4 cell line (15); however, molecular mechanisms mediating its activation remain poorly understood. Chou et al (15) have shown that prolonged treatment of NB4 cells (9 days) with 0.75 M As 2 O 3 markedly up-regulate mRNA levels and membrane expression of p47 phox .…”
Section: Discussionmentioning
confidence: 99%
“…2 demonstrated that capillarization developed over 1-2 weeks of arsenic exposure and was greatly accelerated by arsenic compared to the natural decline in porosity seen in age matched controls. Since arsenite stimulates oxidant production by endothelial cell NAD(P)H oxidase (Smith et al, 2001), it is possible that chronic oxidant stress was responsible for arsenic-induced loss of porosity and phenotypic change in LSEC. However, if this was true, the oxidative stress would have had to be at a low level since total liver hemoxygenase-1 mRNA levels increased by less than 3-fold in following exposure to 250 ppb of arsenite for 5 wks (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…9). Finally, activation of Rac1 and Rac1-NADPH oxidase activity by sodium arsenite initiates a massive production of ROS in cells [61], which is followed by oxidative stress [62], mitochondrial dysfunction and an induction of mitochondrial death pathway in some melanoma lines. In addition, subsequent genotoxic stress also occurs, as well as an up-regulation of p53 protein levels and p53-dependent gene expression, such as BAX and TRAIL-R2 [39,[63][64][65], which is accompanied by an increase in apoptosis and secondary necrosis.…”
Section: Discussionmentioning
confidence: 99%